An evaluation of the restoration programme for a cut over section of Wedholme Flow raised mire - Lewis, Graham (Cranfield University, 2008)
Wedholme Flow, Cumbria is the site of the largest lowland raised mire remaining in the UK. It forms part of a group of ombrotrophic mires known as the Solway mosses, situated in the north west of England. As with all remaining raised mires in the UK, Wedholme Flow has suffered some historical degradation largely caused by cutting of peat at the site’s periphery for fuel. More recently large sections of the mire surface have been commercially mined mainly for horticultural use. These include sections which have been cut over by hand leaving baulks or upstanding strips of unmolested peat between cuttings but also sections of the mire surface that have been strip mined or milled using machinery. Because of the complete loss of Sphagnum the sections of the mire surface that have been milled represent a particular challenge in terms of restoration. The reinstatement of the Sphagnum layer or acrotelm typical of raised mire sites is an important restoration objective. In order for Sphagnum to re-colonise a cut over mire site the water table must remain in close proximity to the surface of the peat throughout the year. The absence of an acrotelm however contributes to seasonal water table fluctuation by decreasing surface storage and allowing increased evaporation from the surface .On cutover mire sites primary restoration efforts centre on raising the water table sufficiently to facilitate Sphagnum re-colonisation and growth with a view to restoring a functioning acrotelm. This study provides a critical appraisal of a restoration programme that aims to raise water levels on a cutover section of Wedholme Flow in Cumbria. The restoration programme was undertaken by Natural England who own and manage the site. Since acquiring the cut-over section of the site bunds and peat plugs have been installed to reduce drainage and raise the water table. Boreholes have been installed on site to monitor changes in water level during and after the restoration. The progress of the restoration programme is evaluated through examination of the water balance, available groundwater data and a review of contemporary literature. Recommendations for further restoration and monitoring are made.
Keywords: lowland raised mire; ombrotrophic mires; historical degradation; unmolested peat; Sphagnum; acrotelm